2018
DOI: 10.1126/sciadv.aat4758
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected contribution of lymphatic vessels to promotion of distant metastatic tumor spread

Abstract: Lymphatic vessels promote organ-to-organ metastasis in addition to mediating tumor cell dissemination from the primary site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 29 publications
(44 reference statements)
2
70
0
Order By: Relevance
“…55,56 Lymphangiogenesis was also shown to occur in distant organs with established metastases where it promoted further spread of the tumor cells to other organs. 57 Supporting the clinical relevance of our findings, we found that expression of Adora2a and adenosinegenerating ectonucleotidases were positively correlated with the levels of lymphatic or pro-lymphangiogenic markers such as Lyve1, Pdpn or Vegfc, in several types of human tumors. In this context, our findings are highly relevant as they identify a novel pathway that could be targeted to block tumor-associated lymphangiogenesis and sentinel lymph node metastasis.…”
Section: Discussionsupporting
confidence: 85%
“…55,56 Lymphangiogenesis was also shown to occur in distant organs with established metastases where it promoted further spread of the tumor cells to other organs. 57 Supporting the clinical relevance of our findings, we found that expression of Adora2a and adenosinegenerating ectonucleotidases were positively correlated with the levels of lymphatic or pro-lymphangiogenic markers such as Lyve1, Pdpn or Vegfc, in several types of human tumors. In this context, our findings are highly relevant as they identify a novel pathway that could be targeted to block tumor-associated lymphangiogenesis and sentinel lymph node metastasis.…”
Section: Discussionsupporting
confidence: 85%
“…Typically, they affect the primary tumor tissue as well as draining collecting vessels and lymph nodes (LNs) which can markedly increase in size during tumor progression . In addition, lymphangiogenesis may also occur at distant metastatic sites, where it correlates with poor outcome in patients with melanoma metastasis to the lung . With regard to breast cancer, clinical studies have revealed that the extent of lymphangiogenesis is very heterogenous, as is the correlation with the clinical outcome, probably reflecting the wide spectrum of breast cancer subtypes which differ extensively in their cellular, molecular and pathological characteristics and prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…3 In addition, lymphangiogenesis may also occur at distant metastatic sites, where it correlates with poor outcome in patients with melanoma metastasis to the lung. 4 With regard to breast cancer, clinical studies have revealed that the extent of lymphangiogenesis is very heterogenous, as is the correlation with the clinical outcome, 1,2 probably reflecting the wide spectrum of breast cancer subtypes which differ extensively in their cellular, molecular and pathological characteristics and prognosis. Nonetheless, a recent meta-analysis including a total of an overall positive correlation between lymphatic vessel density, lymphatic invasion and reduced disease-free and overall survival.…”
Section: Introductionmentioning
confidence: 99%
“…VEGFR-3 reporter mice revealed lymphangiogenesis in lymph nodes, liver, lungs, and spleens of tumor-bearing mice [21] before metastatic spread. High lymphatic density and lymphatic invasion in metastatic lungs was associated with poor outcome of melanoma patients [22]. Blocking pro-lymphangiogenic VEGF-C signaling after cancer cell colonization of tumor-draining lymph nodes prevented further spread to lungs [23] and inhibiting lymphangiogenesis in distant organs may prevent further dissemination of metastatic cells.…”
Section: Timingmentioning
confidence: 99%